Analisis Yurisprudensi terhadap Pertimbangan Hakim dalam Menjatuhkan Pidana Penjara Seumur Hidup atas Tindak Pidana Pembunuhan Berencana Berdasarkan Putusan Mahkamah Agung Nomor 813 K/Pid/2023 - Evan Jagar Lumbanraja; Gusti Bagus Raditya Aryasatya; Ilham Armanda Syahrul; Kallin Intan Ayanti (CV. ITTC INDONESIA, 2026)
Premeditated murder is one of the most serious crimes against life because it is committed intentionally and preceded by careful planning. Consequently, Indonesian Criminal Code (KUHP) prescribes severe sanctions, including the death penalty, life imprisonment, or imprisonment for a maximum term of twenty years. In judicial practice, however, judges do not always impose the death penalty on perpetrators of premeditated murder, even when all legal elements of the offense have been proven beyond reasonable doubt. This phenomenon raises important legal questions regarding the judicial considerations underlying the imposition of life imprisonment and its conformity with sentencing objectives and the principle of proportionality. This study aims to analyze the judicial reasoning in imposing life imprisonment on perpetrators of premeditated murder and to examine the conformity of such decisions with sentencing theories in Indonesian criminal law. The research employs a normative juridical method using statutory and case approaches through the analysis of final and binding court decisions. The study relies on primary, secondary, and tertiary legal materials, which are analyzed qualitatively. The findings reveal that judges base their decisions on the fulfillment of all legal elements of premeditated murder, the high degree of culpability of the offender, the significant social impact of the crime, and the need to protect society. Furthermore, the judges take into account developments in criminal law policy, humanitarian considerations, and substantive justice, leading them to refrain from imposing the death penalty. Life imprisonment is considered the most appropriate sanction because it accommodates the objectives of retribution, deterrence, and social protection in a balanced manner. Therefore, the imposition of life imprisonment in cases of premeditated murder reflects the application of the principle of proportionality and the combined (eclectic) theory of punishment within the Indonesian criminal justice system.